Some Disagreements Existing in the Armenian Linguistics - ZAKARYAN, HOVHANNES (Bulletin of Yerevan University B: Philology, 2021)
Fairly widespread opinions sometimes exist in any field of science which do not adequately reflect the reality and / or cause contradictions in theory and even in practice. This article discusses three linguistic (in particular Armenological) problematic questions concerning the opinions of this kind and having scientific and pedagogical value. As a result of discussion, these questions get the following responses accordingly.1. Nasal resonant sounds ն (n) and մ (m) are not occlusive (plosive) or fricative, but are approximant consonants.2. Synonyms, antonyms, homonyms and paronyms are not kinds of words, but kinds of relation of words in form and meaning.3. The words այսինքն ("i.e."), այն է ("that is") are not coordinative or subordinating conjunctions, but reveal modal particles.
Keywords: nasal resonant, occlusive, fricative, approximant, relation of words in form and meaning, reveal modal particle